Post-traumatic stress disorder among military personnel admitted at the Northwest Command Level Three Military Hospital, Bahir Dar, Ethiopia, 2022: an institution-based cross-sectional study - Tedla, Assasahegn; Asnakew, Sintayehu; Legas, Getasew; Munie, Birhanu Mengist; Tareke, Minale; Beka, Micheal (Frontiers in Psychiatry, 2024)
Background Post-traumatic stress disorder (PTSD) is one of the most common mental health problems that military personnel encounter. It could be lifelong and affect every aspect of military personnel, including their mental and physical health, family and social interactions, and their work. However, in Ethiopia, the magnitude and its associated factors have not been well investigated. Objective This study aimed to determine the prevalence of PTSD and its associated factors among military personnel, who were admitted at the Northwest Command Level Three Military Hospital, Bahir Dar, Northwest, Ethiopia, 2022. Methods An institution-based cross-sectional study was conducted from 21 June to 21 July 2022, at the Northwest Command Level Three Military Hospital. A computer-generated simple random sampling technique was used to select a total of 627 participants. The 17-item Military Version Checklist was utilized to measure PTSD. The Patient Health Questionnaire, Brief Resilience Coping, and Critical War Zone Experience scale were utilized to measure depression, resilience, and combat exposure, respectively. Descriptive, bivariate, and multivariate binary logistic regressions with odds ratios and a 95% confidence interval were used. The level of significance of the association was determined at a p-value < 0.05. Results A total of 612 respondents participated, with a response rate of 97.6%. The prevalence of PTSD in this study was 21.9% (95% CI: 18.6, 25.2). In multivariable regression, female sex [adjusted odds ratio (AOR) = 2.3, 95% CI; 1.3, 3.87], combat personnel (AOR = 2.75, 95% CI; 1.44, 6.36), handling dead bodies (AOR = 2.5, 95% CI,1.24, 5.02), having 4–5 deployments (AOR = 2.94, 95% CI, 1.63, 5.32), having ≥6 deployments (AOR = 3.4, 95% CI, 1.95, 6.17), low resilience coping (AOR = 2.02, 95% CI; 1.16, 3.53), poor social support (AOR = 2.46, 95% CI, 1.39, 4.35), very high combat exposures (AOR = 4.8, 95% CI, 2.03, 11.93), and depression (AOR = 2.8, 95% CI, 1.68, 4.67) were significantly associated with PTSD. Conclusion PTSD is markedly prevalent among the Ethiopian military population, with key risk factors identified as being female, poor social support, low resilience coping skills, handling dead bodies, multiple deployments (four or more), high combat experiences, and depression. Healthcare professionals must prioritize the early diagnosis and intervention of PTSD in vulnerable groups of military personnel.